2019
DOI: 10.1507/endocrj.ej19-0015
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of IL-1β/COX-2/PGE2 pathway loop on islets in type 2 diabetes mellitus

Abstract: The cyclooxygenase2 (COX-2) enzyme catalyzes the first step of prostanoid biosynthesis, and is known for its crucial role in the pathogenesis of several inflammatory diseases including type 2 diabetes mellitus (T2DM). Although a variety of studies revealed that COX-2 played a role in the IL-1β induced β cell dysfunction, the molecular mechanism remains unclear. Here, using a cDNA microarray and in silico analysis, we demonstrated that inflammatory responses were upregulated in human T2DM islets compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
0
28
1
Order By: Relevance
“…In our study, we demonstrated that elevated expression of IL-1b and TNF-a can activate MSCs to secrete IL-1Ra, a requirement for MSCs to restore the function of hT2DM islets. Moreover, IL-1Ra has been shown to inhibit the IL-1 signaling transduction pathway, subsequently preventing damage caused by intermediates such as COX-2 [19] and NF-kB [46,47]. IL-1Ra was also found to reduce the endogenous production of IL-1b in hT2DM islets, possibly due to a feedback loop blockade in IL-1b signallng [48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, we demonstrated that elevated expression of IL-1b and TNF-a can activate MSCs to secrete IL-1Ra, a requirement for MSCs to restore the function of hT2DM islets. Moreover, IL-1Ra has been shown to inhibit the IL-1 signaling transduction pathway, subsequently preventing damage caused by intermediates such as COX-2 [19] and NF-kB [46,47]. IL-1Ra was also found to reduce the endogenous production of IL-1b in hT2DM islets, possibly due to a feedback loop blockade in IL-1b signallng [48].…”
Section: Discussionmentioning
confidence: 98%
“…Diacerein, which decreases both IL-1b and TNF-a demonstrated improved insulin secretion of T2DM patients [17,18]. Moreover, the COX-2 inhibitor Celecoxib was shown to improve insulin secretion of human islets [19]. Together, these studies suggest that targeting the inflammatory response is critical in mitigating b cell dysfunction.…”
Section: Introductionmentioning
confidence: 92%
“…COX 1 and 2), which catalyze the intermediate conversion of PGH2 to PGE2. Elevated islet expression of specific PGE2 synthetic enzymes and/or islet PGE2 excretion has been observed in islets from T2D animals and humans (2,5,6,8,9,20,37). Yet, in this study, PGE2 production was not enhanced in HGOB islets above the levels observed in either lean or NGOB.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the traditional role of Gi/o proteins to block adenylate cyclase activity and reduce cAMP production, EP3γ activity may reduce NGOB β-cell cAMP levels from an even higher theoretical baseline. Numerous signaling changes have been demonstrated in β-cell compensation and failure, such as those mediated by β-cell stress pathways (6,9,38,39), many of which converge on cAMP (14,31,(40)(41)(42). In this scenario, EP3γ up-regulation may be a compensatory adaptation to dampen β-cell stress and promote β-cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation